Detection of antibodies to Toxoplasma gondii in oral fluid from pigs. Issue 5 (May 2020) - Campero, Lucía María; Schott, Franziska; Gottstein, Bruno; Deplazes, Peter; Sidler, Xaver; Basso, Walter
Graphical abstract: Highlights: Antibodies to Toxoplasma gondii were detected in oral fluid from infected pigs by TgSAG1-immunoblot. Most sows had positive immunoblot results for IgA and IgG in oral fluid at 1.5 weeks post inoculation. Fattener groups with 91–92% of seropositive pigs had positive immunoblot results in oral fluid. Fattener groups with ≤13% of seropositive pigs showed negative immunoblot results in oral fluid. Immunoblot on oral fluid allowed detection of high exposure to T. gondii at the farm level. Abstract: Toxoplasma gondii -infected pigs play a major role as a source of infection for humans and detection of high-risk herds is essential to implement control measures at the farm level. The aim of this study was to determine whether oral fluid (OF) could be used as a matrix to detect antibodies against T. gondii in infected pigs by immunoblot (IB). For this, OF from experimentally inoculated sows ( n = 8) (serial samples) and naturally exposed group-housed fatteners ( n = 42 groups, one sample/group) were analysed for IgG and IgA against T. gondii -SAG1 antigen by IB. Simultaneously, each animal was serologically tested for anti- T. gondii IgG by ELISA. Specific IgG was detected in the sera of all inoculated sows from 2 to 3 weeks post inoculation (pi) and in 3.4 to 92% of the pigs in 13 out of 42 groups. Experimentally inoculated sows showed positive OF-IB results for IgA (100%) and IgG (87.5%) at 1.5 weeks pi and continued yielding positive results for IgA (87.5–75%) and IgG (50%) until 4 weeks pi; however, from 8 weeks pi the frequency of detection of both isotypes was lower, despite constantly positive IgG values in serum-ELISA. Interestingly, consecutive daily samplings for 4 days at 13 and 30 weeks pi showed inconsistent results for some sows, showing that the antibody concentration in OF is prone to timely variations. Pooled OF from groups with 91 and 92% of seropositive pigs yielded positive IB results for IgG and IgA. Fattener groups with ≤13% of seropositive pigs gave negative IB results to both isotypes. Our results showed that antibodies to T. gondii can be detected in OF from infected pigs, and that IgA seems to be a more adequate target than IgG. Although OF does not seem to be a robust matrix to assess the serological status for T. gondii in individual animals, this diagnostic approach represents an interesting non-invasive, low-cost and animal welfare friendly option as a screening method at the farm level to determine high exposure to T. gondii in the herd.